A TYPICAL CASE OF HYDRAMNIOS ACCOMPANIED WITH FETAL MONSTROSITY (PROGNATHISM) IN A NON DESCRIPT COW - SHARMA, UTSAV; KUMAR, SUDHIR; KUMAR, SHARAD (The Indian Journal of Animal Reproduction, 2023)
A successful management of hydroamnions in full term local cattle and delivery of a live male calf withhead monstrosity through obstetrical mutation and forced traction is reported.
Keywords: Hydramnios; fetal monstrosity; cow